POLICE OPERATIONS IN THE FIELD OF PROVIDING SECURITY OVER RAILWAY AREAS IN POLAND - Jacek DWORZECKI (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The aim of this paper is to present the role of the police in providing security in the territories and railway areas in Poland. The statutory tasks and forms of their implementation by the formation have been discussed, in the context of monitoring the safety and the prevention of and response to crimes occurring on railway. The text has used available literature which examines the biggest problems of functioning of the police formations in the country, as well as publicly available statistics on the state of security in the Polish railway stations, bus stops and railway stations and passenger trains and freight services. The level of security of the rest of the railway infrastructure has also been analyzed. The text is enriched with information from expert interviews which allowed to deepen the knowledge already available on the forms and methods of criminal activities that take place in areas and railway premises. Based on the empirical results obtained, characterized (in outline) in this publication, you may be tempted to say that the security situation in the sector of social life is gradually increasing, which undoubtedly has been influenced by the actions and initiatives taken by the state formations in uniform, established to protect public order and safety in Poland. The publication is a supplement to the state of knowledge about the activities, engagement and work outcomes of the police, which is very important, both from social and economic point of view, and for the functioning of our country as a whole.